Tertiary lymphoid structures in the microenvironment of colorectal cancer: exploring new therapeutic targets - Nan-Nan Dai; Man-Yi Hu; Jian-Ping Wang; Zhi-Hui Dai; Li Xu; Tai-Wei Ye (Cancer Immunology, Immunotherapy)
Abstract Immunotherapy has shown limited efficacy in colorectal cancer (CRC), necessitating the urgent identification of novel immunotherapeutic targets to address this challenge. Tertiary lymphoid structures (TLSs) are complex immune structures that spontaneously form within and outside of the tumor microenvironment, resembling secondary lymphoid organs. The formation of TLS formation dynamically adapts to the tumor microenvironment, with their immune function maintained by resident immune cells and cytokine networks. TLS develops antitumor immune competence following dynamic reorganization of their cellular components and proportions, although the precise mechanistic underpinnings remain to be fully characterized. Numerous studies have demonstrated that TLS can modulate the immune status of CRC, potentially enhancing the efficacy of immunotherapy. Currently, the clinical setting lacks appropriate immunological markers to assess immunotherapy outcomes, and TLS may offer a solution to this limitation. This article will review current research on TLS as a novel therapeutic target in the immunotherapy of malignant colorectal tumors.